2016
DOI: 10.1137/15m1017569
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Sublinear Separators and Polynomial Expansion

Abstract: A result of Plotkin, Rao, and Smith implies that graphs with polynomial expansion have strongly sublinear separators. We prove a converse of this result showing that hereditary classes of graphs with strongly sublinear separators have polynomial expansion. This confirms a conjecture of the first author. *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 11 publications
2
68
0
Order By: Relevance
“…A very different approach is taken by Cabello and Gajser [3] for proper minor-closed classes and more generally by Har-Peled and Quanrud [20] for classes of graphs with polynomial expansion (which by the result of Dvořák and Norin [13] is equivalent to having strongly sublinear separators). They showed that the trivial local search algorithm (performing bounded-size changes on an initial solution as long as it can be improved by such a change) gives polynomial-time approximation schemes for maximum independent and minimum dominating set, as well as many other related problems.…”
Section: Related Resultsmentioning
confidence: 99%
“…A very different approach is taken by Cabello and Gajser [3] for proper minor-closed classes and more generally by Har-Peled and Quanrud [20] for classes of graphs with polynomial expansion (which by the result of Dvořák and Norin [13] is equivalent to having strongly sublinear separators). They showed that the trivial local search algorithm (performing bounded-size changes on an initial solution as long as it can be improved by such a change) gives polynomial-time approximation schemes for maximum independent and minimum dominating set, as well as many other related problems.…”
Section: Related Resultsmentioning
confidence: 99%
“…It was recently shown that any graph with strongly sublinear hereditary separators has polynomial expansion [DN15]. In conjunction with the preceding separator (for low-density objects), this yields a second proof that the intersection graphs of low-density objects have polynomial expansion, however with weaker bounds.…”
Section: Separatorsmentioning
confidence: 90%
“…Using the existence of good 3-regular expanders, Dvořák and Norin [22,Corollary 7] find a family of 3-regular graphs on k edges and n = Instead of relying on Proposition 1.6 to count homomorphisms in Theorem 1.1, we can use more sophisticated methods where available. For instance, we can use fast matrix multiplication to count homomorphisms from patterns H of treewidth at most two, thus proving Theorem 1.3.…”
Section: To Obtain #Sub(h → G)mentioning
confidence: 99%